TANGGUNG JAWAB PENGANGKUT TERHADAP KORBAN KECELAKAAN JALAN TOL (ANALISIS PUTUSAN NOMOR 308/PDT.G/2020/PN.JKT.PST) - Salsabila Setyaningrum; Siti Nurbaiti (Reformasi Hukum Trisakti, 2021)
Traffic accidents, especially on the JORR Toll Road still occur frequently, sometimes involving third parties, for example in the case of a traffic accident that occurred between a truck and a PJR (Highway Patrol) Service Car on the JORR Toll Road (Ciledug area towards Meruya), South Jakarta. Problem formulation: How is the Responsibility of Truck Carriers for accident victims at the JORR Toll Road in South Jakarta based on Law No. 22 of 2009 and whether the Judge's Decision Number 308/Pdt.G/2020/PN.Jkt.Pst regarding the Responsibility of Truck Carriers is in accordance or not with Law No. 22 of 2009. The research method used is descriptive normative research method by sourcing secondary data, which is analyzed qualitatively with descriptive conclusions. The results of the research, discussion and conclusion that the transportation company is not responsible as stipulated in Article 194 of the UULLAJ and the Judge's Decision is not in accordance with the road traffic and transportation law because it decides based on Article 1367 of the Civil Code.